Cost Analysis of a High Support Housing Initiative for Persons with Severe Mental Illness and Long-Term Psychiatric Hospitalization - Rudoler, David (Can J Psychiatry, 2018)
OBJECTIVE: The objective of this article was to conduct a cost analysis comparing the costs of a supportive housing intervention to inpatient care for clients with severe mental illness who were designated alternative-level care while inpatient at the Centre for Addiction and Mental Health in Toronto. The intervention, called the High Support Housing Initiative, was implemented in 2013 through a collaboration between 15 agencies in the Toronto area. METHOD: The perspective of this cost analysis was that of the Ontario Ministry of Health and Long-Term Care. We compared the cost of inpatient mental health care to high-support housing. Cost data were derived from a variety of sources, including health administrative data, expenditures reported by housing providers, and document analysis. RESULTS: The High Support Housing Initiative was cost saving relative to inpatient care. The average cost savings per diem were between $140 and $160. This amounts to an annual cost savings of approximately $51,000 to $58,000. When tested through sensitivity analysis, the intervention remained cost saving in most scenarios; however, the result was highly sensitive to health system costs for clients of the High Support Housing Initiative program. CONCLUSIONS: This study suggests the High Support Housing Initiative is potentially cost saving relative to inpatient hospitalization at the Centre for Addiction and Mental Health.